Systematic calculation of threshold displacement energies: Case study in rutile - Robinson, Marc; Marks, Nigel; Whittle, K.; Lumpkin, G. (American Physical Society, 2012)
A generalized and systematic method of calculating threshold displacement energies (Ed ) using molecular dynamics simulations has been developed and applied to rutile TiO2. Statistically representative results have been achieved through fine sampling of impact energy and trajectory for each atomic species. Each impact trajectory is drawn from a uniform distribution of points on a unit sphere, along which, primary knock-on atoms (PKAs) with kinetic energies in the range of 20–200 eV were introduced into lattices equilibrated to 300 K. Various definitions of Ed are explored, with values presented as probabilities of defect formation. Results for the Ti PKA agree well with experimental data with a value of Ed at around 69 eV. Simulations of O PKAs contrast greatly with Ti PKAs, with displacements occurring at significantly lower energies, resulting in an O value of Ed at 19 eV. Analysis shows that replacement chains on the O sublattice are a common feature and play a significantrole in governing defect formation in rutile.